Production performance of Hylocereus polyrhizus based on cladode size and position - Pereira da Silva Brito, Leonardo; Rosario de Oliveira, Ellison; Dionizio Luiz, Paulo Henrique; Ramos, José Darlan; Ferreira de Almeida, Letícia Gabriela; Andrade Dos Santos, Verônica (Comunicata Scientiae, 2024)
The analysis of productive architecture of plants involves macroscopic observation of spatial distributions of different vegetative and reproductive organs. However, few studies have evaluated these aspects in dragon fruit plants for production purposes. The objective of this study was to evaluate vegetative, reproductive, and quality parameters of dragon fruit plants (Hylocereus polyrhizus; variety Cebra) based on the position and size of cladodes, considering morphological, production, and quality characteristics of the fruits. The experiment was conducted from September 2016 to May 2018, using a completely randomized design in a 3×4 factorial arrangement, consisted of three positions of cladode insertion in the plant (primary, secondary, and tertiary) and four different cladode sizes (≤ 20 cm; 21-40 cm; 41-60 cm, and 61-80 cm), with five replications and six cladodes per plot, totaling 360 evaluated cladodes. According to the results, vegetative and reproductive characteristics of dragon fruit plants variety Cebra were affected by the cladode position and size. Fruits developed on primary cladodes with sizes of 21 to 40 cm presented, in general, better-quality characteristics. All evaluated physical and physicochemical characteristics were affected by the cladode position and size, except for titratable acidity and soluble solids to titratable acidity ratio. Fruits developed on cladodes smaller than 20 cm had lower quality. Therefore, maintaining and promoting the growth of primary cladodes with sizes of 21 to 40 cm and removing those smaller than 20 cm is recommended.